Ecosystem mapping for the implementation of the European Biodiversity Strategy at the national level: The case of Italy. Issue 78 (December 2017) - Blasi, Carlo; Capotorti, Giulia; Alós Ortí, Marta María; Anzellotti, Ilaria; Attorre, Fabio; Azzella, Mattia Martin; Carli, Emanuela; Copiz, Riccardo; Garfì, Vittorio; Manes, Fausto; Marando, Federica; Marchetti, Marco; et al.
Highlights: An original approach for mapping ecosystems at the national level is presented. Current and potential vegetation are adopted as valuable ecosystem proxies. The resulting Italian map is much more detailed than available EU-level syntheses. The map is effectively supporting main BD conservation initiatives in Italy. It represents the knowledge base for the national Natural Capital Accounting system. Abstract: Several international initiatives, including the European Biodiversity Strategy to 2020, promote the identification and mapping of ecosystems as basic tools for the conservation of biodiversity and related services. On coarse scales, the spatial representation of ecosystems is usually based on broad land cover categories that largely overlook important ecological and biogeographic features of the biotic communities they are meant to exemplify. This paper presents a nationwide ecosystem mapping approach that promotes a degree of thematic detail, which is more suited than that found in the continental maps to meeting biodiversity conservation targets in Italy. The approach is based on the rationale that current and potential vegetation cover are valuable proxies for outlining ecosystems. The resulting Ecosystem Map of Italy includes 43 types of forest ecosystems instead of the 5 woodland, forest and other wooded land types recognized at the European level. We outline the expected advantages of this enhanced thematic detail for a number of conservation purposes and highlight how the resulting maps may help to meet biodiversity conservation targets at the national level. In particular, we refer to the assessment of conservation status, the definition of restoration priorities, the planning of green infrastructure and the identification of collapse risks for the ecosystems identified. Comprehensively, the definition, characterization and assessment of ecosystem types represent the carrying structure of the recently launched national system of natural capital accounting.